Strategi Kepala Madrasah dalam Pengelolaan Konflik Siswa di MAS Jeumala Amal Pidie Jaya - Nurussalami, Nurussalami; Abra, Nabil Aisar; Yusrijal, Yusrijal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
School behavior strategies In managing student conflict, it involves a deep understanding of the sources of conflict, the application of communicative approaches, and the formation of an environment that supports conflict resolution.madrasah heads need to promote open dialogue, involve stakeholders and be able to implement proactive policies in creating a harmonious and warm and inclusive learning atmosphere. The purpose of this study was to find out the head of the madrasah in managing conflicts that occur between students at MAS Jemala Amal, namely planning, and constraints in conflict management. Remembering conflict is a sensitive topic and often intersects with one's emotions. The method that researchers use is to use qualitative methods by means of a descriptive approach through observation, interviews and documentation. The research subjects of madrasah heads, Guidance Counseling teachers, homeroom teachers and Students. The results of research obtained by researchers in the field include: First, Student conflict management includes: (a) madrasah heads and teachers are quite creative and understand appropriate conflict management strategies in managing conflicts that occur among students in madrasahs. (b) The madrasah identifies problems in advance or examines problems that occur between students. (c) provide coaching. (d) seeking the relevant parties. (e) evaluation of problems that have occurred. Second, constraints in managing student conflicts as follows: (a) social environment. (b) personality differences between learners. (c) not tell what actually happened.